Social Media in Practice Digital Literacy Among Parents - Satunggale Kurniawan; Chusnul Chabibah Ilhama (Journal of Cultural Narratives in Digital Society, 2026)
This study aims to analyze the role of social media in improving digital literacy practices among parents in the digital era. A qualitative descriptive approach was employed to gain a deeper understanding of parents’ experiences, perceptions, and habits in using social media. The research subjects consisted of parents actively using social media platforms such as WhatsApp, Facebook, and Instagram, selected through purposive sampling. Data were collected through in-depth interviews, observations, and documentation. The findings indicate that social media significantly contributes to improving parents’ digital literacy by increasing their ability to use digital features, access information, and understand digital security and privacy. Social media also serves as an informal learning medium through online communities and parenting groups that facilitate knowledge sharing and interaction. However, several challenges remain, including difficulties in distinguishing valid information from misinformation and limited technological understanding among some parents. Family support, especially from children, also contributes positively to improving parents’ digital skills. Therefore, continuous education and guidance are needed to ensure parents use social media wisely, safely, and effectively.